2018
DOI: 10.1172/jci.insight.122268
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and chemokine signatures associated with hepatitis B surface antigen loss in hepatitis B patients

Abstract: RESULTS.In AH patients and HBV-inoculated chimpanzees with HBsAg loss, CXCL9, CXCL10, CXCL11, CXCL13, and IL-21 were elevated at hepatitis with subsequent decline of HBsAg. Interestingly, IL-21 elevation was observed only in resolving AH patients but not in nonresolvers. CXCL13 and IL-21 elevation was not observed in CH patients who failed to attain HBsAg loss, even at hepatic flare. A concomitant increase of CXCL13 and IL-21 was significant in CH patients who attained HBsAg seroconversion with a sequential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…( 15,21 ) Moreover, the frequency of circulating T FH and systemic levels of T FH ‐associated cytokines and chemokines (IL‐21, chemokine [C‐X‐C motif] ligand 13 [CXCL13]) are associated with immune control in patients with HBV. ( 16,17,22 ) Because TLR8 agonists promote T FH differentiation through production of IL‐12 ( 9 ) and directly inhibit Treg function, ( 4 ) our data suggest that GS‐9688 may induce effective antiviral immunity by augmenting a preexisting T FH response in the liver (Supporting Fig. ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…( 15,21 ) Moreover, the frequency of circulating T FH and systemic levels of T FH ‐associated cytokines and chemokines (IL‐21, chemokine [C‐X‐C motif] ligand 13 [CXCL13]) are associated with immune control in patients with HBV. ( 16,17,22 ) Because TLR8 agonists promote T FH differentiation through production of IL‐12 ( 9 ) and directly inhibit Treg function, ( 4 ) our data suggest that GS‐9688 may induce effective antiviral immunity by augmenting a preexisting T FH response in the liver (Supporting Fig. ).…”
Section: Discussionmentioning
confidence: 89%
“…Various studies have identified a potential role for IL-21 in the immune control of HBV infection (14)(15)(16), and it is therefore striking that baseline intrahepatic IL21 expression was significantly elevated in antiviral responders (Fig. 7D).…”
Section: Baseline Intrahepatic Transcriptional Profile Differentiatesmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, in progressive AHB there were very low to undetectable circulating cytokine levels in spite of persistently high levels of viremia since the very first weeks postinoculation, with values of HBV DNA higher than 8 log 10 IU/ml. In a recent study conducted in acute resolving versus acute progressing hepatitis B in humans, Yoshio et al found that resolving hepatitis was associated with higher levels of CXCL9, CXCL10, CXCL11, CXCL13, and IL-21 at ALT peak (39). They also showed that levels of the same cytokines were remarkably lower during a flare of hepatitis in chronic HBV infection, which is characterized by an exhaustion of HBV-specific T cells (40).…”
Section: Discussionmentioning
confidence: 98%
“…In general, cytotoxic mechanisms for HBV-specific CD4+ and CD8+ T cells and noncytotoxic mechanisms for IFN-γ and TNF-α, which are produced by natural killer (NK) cells, are detectable in acute hepatitis B patients [ 17 , 18 ]. Activated NK cells can activate CD4+ and CD8+ T cells, DCs and NK T cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%